The Practice of Formative Assessment in College English Teaching - liu, yu (Pacific International Journal, 2022)
With the increasing demand for a higher level of college English teaching, a proper way of evaluation, which is a vital part for the whole process of teaching, is in great need. As an effective method of teaching evaluation, formative assessment has attract great concern among professors and scholars and is now extensively being applied to college English teaching, contributing to the effective implementation of college English teaching evaluation. Based on the present situation of college English teaching, this paper analyzes the challenges and problems that college English teaching is facing and tries to put forward some practical paths to integrate formative assessment into present college English teaching.